Respuesta :
The expression [tex]2x+(x-7)^2[/tex] is equivalent to [tex]x^2+bx+49[/tex].
Then Value of b is - 12.
Option(B) is correct answer.
What is an expression?
An expression is a mathematical phrase combining numbers and/or variables using mathematical operations. Both sides of an equation are expressions.
According to the question,
The expression [tex]2x+(x-7)^2[/tex] is equivalent to [tex]x^2+bx+49[/tex].
[tex]2x+(x-7)^{2}=x^{2} +bx+49[/tex]
⇒ [tex]2x+(x-7)^{2}=x^{2} +bx+49[/tex]
⇒[tex]2x+x^{2} -14x+49=x^{2} +bx+49[/tex]
⇒ [tex]x^{2} -12x+49=x^{2} +bx+49[/tex]
⇒[tex]-12x=bx[/tex]
⇒ [tex]b=-12[/tex]
∴ [tex]b=-12[/tex]
Hence, the expression [tex]2x+(x-7)^2[/tex] is equivalent to [tex]x^2+bx+49[/tex].
Then Value of b is - 12.
Option(B) is correct answer.
Learn more about expression here
https://brainly.com/question/19131200
#SPJ2